The voice of the self: a typology of general practitioners' emotional responses to situational and contextual stressors. (3rd April 2022) - Johnsson, Linus; Nordgren, Lena
Abstract: Objective: To develop a comprehensive typology of emotional reactions associated with stress among general practitioners (GPs), grounded in their own experiences. Design: Data was generated using observations and unstructured interviews, using Straussian grounded theory as the overarching methodology. The typology was built using multidimensional property supplementation. Setting: Eleven health care centres in urban and rural communities in four Swedish regions. Subjects: Sixteen GPs and GP residents. Main outcome measures: Characteristics of GPs' emotional reactions in everyday work situations. Results: Accounts of negative emotions connected to stress revealed four principal personal needs of the GP: trust, efficacy, understanding, and knowledge. Simultaneous threats to more than one of these needs invariably increased the level of tension. From these more complex accounts, six second-order needs could be identified: integrity, judgment, pursuit, authority, autonomy, and competence. The most extreme encounters, in which all four principal needs were threatened, were characterised by the experience of being reduced into an assistant. Conclusion: The considerable resilience of GPs may belie some of the pressures that they are facing while being far from a fail-safe defence against being diverted from purposeful and morally responsible action. Our typology distinguishes between different forms of stress that may affect how GPs carry out their work, and connects to the vast literature on GP wellness. The results of this study could be used to develop tools for self-reflection with the aim of countering the effects of stress, and are potentially relevant to future research into its causes and consequences. Key points: What is known Stress among GPs may have severe consequences for themselves and their patients, and levels of stress appear to be increasing. What this article adds Stressful situations threaten at least one of four principal needs of the GP: trust, efficacy, understanding, and knowledge. More complex threats increase the level of tension and bring out second-order needs: integrity, judgment, pursuit, authority, autonomy, and competence. The wealth of literature on GP stress can be clearly understood through the lens of our four-dimensional typology.